2019
DOI: 10.1038/s41598-019-46247-z
|View full text |Cite
|
Sign up to set email alerts
|

A highly responsive NH3 sensor based on Pd-loaded ZnO nanoparticles prepared via a chemical precipitation approach

Abstract: The gas-detecting ability of nanostructured ZnO has led to significant attention being paid to the development of a unique and effective approach to its synthesis. However, its poor sensitivity, cross-sensitivity to humidity, long response/recovery times and poor selectivity hinder its practical use in environmental and health monitoring. In this context, the addition of noble metals, as dopants or catalysts to modify the ZnO surface has been examined to enhance its sensing performance. Herein, we report prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(55 citation statements)
references
References 49 publications
2
53
0
Order By: Relevance
“…The mean diameter of the Fe/Pd NPs was measured to be 10.1 ± 1.7 nm (Figure 2c), indicating that the filter paper employed in this study is a good substrate for the growth and assembly of bimetallic Fe/Pd NPs. High-resolution TEM image reveals the lattice structure of the NPs, and the d spacing was calculated to be 0.204 nm and 0.23 nm, corresponding to the [110] plane of α-Fe 0 and the [111] plane of the face-centered cubic crystal structure of Pd, respectively [24,25]. Furthermore, energy-dispersive spectrum (EDS) shows clearly the signals of Pd and Fe elements, confirming the bimetallic nature of the Fe/Pd NP-assembled filter paper.…”
Section: Resultsmentioning
confidence: 99%
“…The mean diameter of the Fe/Pd NPs was measured to be 10.1 ± 1.7 nm (Figure 2c), indicating that the filter paper employed in this study is a good substrate for the growth and assembly of bimetallic Fe/Pd NPs. High-resolution TEM image reveals the lattice structure of the NPs, and the d spacing was calculated to be 0.204 nm and 0.23 nm, corresponding to the [110] plane of α-Fe 0 and the [111] plane of the face-centered cubic crystal structure of Pd, respectively [24,25]. Furthermore, energy-dispersive spectrum (EDS) shows clearly the signals of Pd and Fe elements, confirming the bimetallic nature of the Fe/Pd NP-assembled filter paper.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, abundant negative charges can be captured by the oxygen molecules attached to the surface of the nanorods. This process forms a depletion layer on the surface around of ZnO nanorods [17][18][19][20][21][22]. Therefore, the Pd/ZnO sample exhibits a lower current than the ZnO sample in darkness.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to noble metal nanoparticles (NPs; e.g. Au, Pt and Pd), modified ZnO nanostructures are used often in the field of chemical sensing, such as in CH4, NH3, H2, NO2, CO and organic gas sensors [17][18][19][20][21][22]. Several studies investigate UV photodetector applications with Au and Pt NP-modified ZnO nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the HRG-Py-Pd gave sharp peaks for Pd centered at 337.9 eV, 343.2 eV respectively, indicating the presence of only Pd 0 . The difference of binding energy being 5.3 eV is indicative of existence of Pd 3d 5/2 and Pd 3d 3/2 of Pd(0) in the HRG-Pd and HRG-Py-Pd composite 40 . Upon examination of the reused catalyst using XPS, it was found that there is no change in the intensity and oxidation state of the Pd nanoparticles deposited on the HRG-Py-Pd.…”
Section: Vol:(0123456789)mentioning
confidence: 99%